Urgensi Media Massa Dalam Mensosialisasikan Himbauan Vaksinasi Covid-19 Di Masa Pandemi - Siti Wuryan; Muhamad Bisri Mustofa; Muhamad Juniardi; Khilda Nur Kholisiyah; Juwita Nindy Rosiana (AL-IDZA'AH: Jurnal Dakwah dan Komunikasi, 2022)
The mass media actually has an important role in disseminating information or in terms it can be said as an agent of socialization, this is very important if applied to convey appeals related to Covid-19 vaccination in the pandemic era to all levels of society. Previous research has stated that the mass media plays an important role as agents of ideological socialization and political passion to young people, and other studies explain the role of print media in disseminating the vaccination appeal. This paper refers to mass media coverage, social media, journal articles, and all resources that can be accessed online, or using library research methods. This paper explains how the mass media are able to become agents of socialization, especially in conveying appeals regarding vaccination policies in the pandemic era at various levels of society regardless of all the dynamics and obstacles that become obstacles.